2023
DOI: 10.3389/fmed.2023.1260312
|View full text |Cite
|
Sign up to set email alerts
|

ICU nurses’ knowledge and attitude towards electrocardiogram interpretation in Fujian province, China: a cross-sectional study

Salome E. Buluba,
Jinyi He,
Hong Li

Abstract: IntroductionThe series of electrocardiograms (ECGs) can help track cardiac abnormalities in patients’ conditions and make an earlier clinical decision. It is crucial for nurses working in critical care environments to acquire ECG knowledge for effective ECG monitoring and act accordingly in case of a change in patient condition. This study aimed at investigating intensive care unit (ICU) nurses’ knowledge and attitude towards ECG interpretation in Fujian province, China. The study also analyzed the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This nding is in consistent with Shehab et al [20] who studied the effect of an educational program of electrocardiogram interpretation on medical and maternity nurses' knowledge and skills and found no statistically signi cant association between sociodemographic data of the study group and their total knowledge score throughout the educational program. However, another study was conducted by Buluba et al [4] and showed contradicting ndings where they indicated that all the demographics of the participants nurses showed signi cant association with the ECG knowledge level.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…This nding is in consistent with Shehab et al [20] who studied the effect of an educational program of electrocardiogram interpretation on medical and maternity nurses' knowledge and skills and found no statistically signi cant association between sociodemographic data of the study group and their total knowledge score throughout the educational program. However, another study was conducted by Buluba et al [4] and showed contradicting ndings where they indicated that all the demographics of the participants nurses showed signi cant association with the ECG knowledge level.…”
Section: Discussionmentioning
confidence: 91%
“…In con rmation of the researcher's point of view, Jablonover et al, reported that the level of competency in ECG interpretation was previously found to be correlated with the degree of ECG exposure [30]. According to Buluba et al, frequent exposure to ECG interpretation facilitates retention of knowledge [4]. As well, Chen et al documented that it is expected that low competency will be observed in ECG patterns that are less commonly encountered by students, and vice versa [18].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Timely identification and management of life-threatening arrhythmias by nurses can reduce mortality rates and improve patient outcomes [ 12 ]. A study shows that most practicing nurses exhibit a positive attitude towards the diagnosis of arrhythmias, but the majority demonstrate a lower level of proficiency in arrhythmia diagnosis [ 13 ]. Another study found that nursing students have a certain gap compared to practicing nurses in both theoretical knowledge and practical skills [ 14 ].…”
Section: Introductionmentioning
confidence: 99%